ROLE OF FLUID ON THE CONTACT DEFORMATION RESPONSE OF BIOLOGICAL TISSUE - Michael V. Swain (Acta Polytechnica CTU Proceedings, 2020)
This paper will focus on the role of fluids on the indentation deformation response of tooth and eye tissues. All natural biological materials contain fluid and function in a fluidic environment, which plays a critical role in responding to loading events as well as tissue nutrition. The location of this fluid varies and is considered as both bound and mobile with much of it located in cell compartments that are also able to respond directly to loading. The extent of the fluid content varies from less than 10 % in the case of the highly mineralised enamel to more than 80 % in the case of soft eye tissues. The role of the fluid and its response during loading is also complicated by the hierarchical structure of biological tissues, be they mineralised or not. The mechanisms by which the presence of fluid in these materials influences the mechanical response is still poorly understood and has not been systematically investigated. The present paper presents data generated over many years on both the above biological tissues and attempts to present indications as to the mechanism(s) by which the presence of fluid contributes to the deformation. The situation associated with contact loading with the presence of mobile fluid in the tissues results in a more complex situation than the classic elastic-plastic contact situation, but the latter still forms the basis for much of the analysis of instrumented indentation force-displacement load-unloading curves using various shapes of indenters, especially for mineralised structures. In the case of soft tissues the absence of agreed protocols for interpretation of force-displacement-time responses is restricting clinical/biological applications.